First record of Simognathus (Acari: Halacaridae) from Mexico, including the description of a new species - Rivas, Gerardo (Zootaxa, 2006)
This is the first record of the genus Simognathus and of the subfamily Simognathinae from Mexico. Simognathus cramerae sp. nov. is described from the Mexican tropical Pacific Ocean. The principal diagnostic features are dorsal setae 2 outside of ocular plate, dorsal setae 3 on anterodorsal plate, and second segment of pedipalp with a ventral bristle and without a ventral apophysis. This species resembles S. fuscus Viets, S. similis Bartsch, and S. hulingsi Newell.